Development and User Evaluation of a Food-recognition app (FoodRec): Experimental Data and Qualitative Analysis - Sebastiano Battiato; Pasquale Caponnetto; Roberto Leotta; Giovanni Marotta; Alessandro Midolo; Alessandro Ortis; Riccardo Polosa (Health Psychology Research)
# Background